Africon 2009 2009
DOI: 10.1109/afrcon.2009.5308173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variation in modelling of generator saturation on electromechanical modes

Abstract: Several industrial-grade power system simulation tools are commercially available in the market. They are expensive to acquire and time-consuming to learn. As a result, very few institutions (utilities, academiclresearch organizations) can afford to use more than one power system simulation tool. The simulation tools differ in their components modelling. Different simulation tools can give different results for the same system model. Understanding the reasons for the discrepancies in the results is not a trivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The 6 th order generator model was used to represent the generator G1. System data can be found in [4], [14], [17].…”
Section: Simulation Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 6 th order generator model was used to represent the generator G1. System data can be found in [4], [14], [17].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Previous investigations have indicated that L ads(incr) could be equal to or less than 50% of L adu [14]. This method of representing saturation is applicable to machine models represented using the coupled-circuit method.…”
Section: Bmentioning
confidence: 95%
See 3 more Smart Citations